CIRCULAR ECONOMY AGENCY IN THE SMARTPHONE SECTOR IN THE EUROPEAN UNION: A SOCIOLOGICAL ANALYSIS - Heikkinen, Eeva (My University, 2025)
This thesis explores circular economy (CE) agency in the European Union (EU) smartphone sector. Given smartphones’ exceptional impact on the lives of individuals and communities and their environmental effects, actions supporting sustainable development are essential. Transitioning from a linear to a circular economy is a key strategy for enhancing sustainability. This transition can be driven by the efforts of various CE agency types. Therefore, this thesis employs a rapid review method to examine which CE agency types are identifiable in the EU smartphone sector. The results inform a theoretical synthesis, grounded in the theories of Giddens’ (1984) and Archer (1988), exploring how structures and culture both shape and are shaped by these forms of CE agency. The results indicate that Companies’ Agency and Agency via Ecosystem are particularly potential contributors of the CE transition. Also, CE agency should especially be exercised in the context of E-Waste Management & Resource Recovery, but also in Systemic and Economic Strategies. In the synthesis, the findings are analysed and illustrated with multiple examples in the contexts. Various AI-tools have been utilized creating this thesis, to explore new perspectives, support initial analyses, and refine written text. All results are validated and verified by the author.
Keywords: Circular Economy Agency, Smartphone, Circular Economy, European Union, Structure, Culture, Sociology